2011
DOI: 10.1128/jvi.02577-10
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6 Suppresses T Cell Proliferation through Induction of Cell Cycle Arrest in Infected Cells in the G 2 /M Phase

Abstract: Human herpesvirus 6 (HHV-6) is an important immunosuppressive and immunomodulatory virus that primarily infects immune cells and strongly suppresses the proliferation of infected cells. However, the mechanisms responsible for the regulation and suppression mediated by HHV-6 are still unknown. In this study, we examined the ability of HHV-6A to manipulate cell cycle progression in infected cells and explored the potential molecular mechanisms. We demonstrated that infection with HHV-6A imposed a growth-inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 55 publications
1
56
0
Order By: Relevance
“…Upregulation expression of p21, an important cell cycle arrest factor, was further verified by real-time PCR analysis. The increased expression of p21 in infected cells was also found in other herpesviruses [31,32]. …”
Section: Discussionmentioning
confidence: 93%
“…Upregulation expression of p21, an important cell cycle arrest factor, was further verified by real-time PCR analysis. The increased expression of p21 in infected cells was also found in other herpesviruses [31,32]. …”
Section: Discussionmentioning
confidence: 93%
“…HHV-6 is an important immunosuppressive and immunomodulatory virus which can induce immunomodulation through a variety of mechanisms, such as lytic infection of CD4 ϩ and/or cytotoxic effector T cells, impairment of antigen-presenting cell functions, induction of inflammatory and immunosuppressive cytokines and/or chemokines, and downmodulation of the CD3/T cell receptor complex (9,10). Our recent studies have demonstrated that HHV-6A infection induced cell cycle G 2 /M arrest in infected T cells via various molecular regulatory processes, further suggesting that this potential mechanism involved in its immune suppression and modulation (11). However, the mechanisms responsible for the regulation and suppression mediated by HHV-6 infection are still under investigation.…”
mentioning
confidence: 99%
“…Like most herpesviruses, HHV-6 can establish long-term latency in its hosts using immunomodulatory mechanisms to evade the immune system. HHV-6 is indeed known to infect T cells very efficiently and to reduce their proliferation (29)(30)(31), and some viral proteins have been shown to inhibit signaling pathways involved in immune responses (32)(33)(34). However, HHV-6 is also able to promote inflammation by inducing the development of a Th1 phenotype in T cells (35,36), enhancing the cytotoxicity of NK cells (37), and by increasing the production of proinflammatory cytokines and chemokines in different cell types (38,39).…”
mentioning
confidence: 99%